Pengaruh Nisbah Bagi Hasil dan Jaringan Kantor terhadap Minat Masyarakat Menabung - Gunawan, Nazali; Rani Pertiwi, Ruspita (Masoem University, 2025)
This study aims to analyze the effect of profit-sharing ratio and office network on public savings interest in Islamic banking which is proxied using the number of users accounts, during the 2020-2024 period both partially and simultaneously. This study employs a descriptive quantitative methodology, using secondary data obtained as time series. The research data uses the financial reports of all Islamic banking for the years 2020-2024, which were summarized from the Financial Services Authority. The data analysis technique uses the classical assumption method and multiple linear regression. The results of this study indicate that the profit-sharing ratio and office network partially have a significant effect on public savings interest. The results simultaneously show that the profit-sharing ratio and office network have a significant effect on public savings interest in Islamic banking.